The use of learning strategies: Do distinctive groups of learners exist? - Rita C. Kolody; Gary J. Conti (Adult Education Research Conference, 1996)
Learning strategies were examined in a province-wide study involving five colleges throughout Alberta. Several multivariate analyses using discriminant analysis failed to produce any powerful functions although weak differences were found in the areas of grades, gender, program, and age. The multivariate technique of cluster analysis, however, did produce a solution with five clear and distinct clusters of learners.